Disseminated trichosporonosis with atypical histologic findings in a patient with acute lymphocytic leukemia. (18th December 2018) - Galligan, Eloise R.; Fix, Lindsey; Husain, Sameera; Zachariah, Philip; Yamashiro, Darrell J.; Lauren, Christine T.
Abstract : We report a case of disseminated Trichosporon asahii in a patient on systemic antifungal therapy who presented with multiple cutaneous nodules suggestive of fungal infection. Histologic features resembled neutrophilic eccrine hidradenitis but staining with periodic acid‐Schiff and Gomori methenamine silver confirmed the clinical diagnosis. This case highlights the importance of maintaining suspicion for trichosporonosis and contextualizing histologic findings within the underlying clinical picture.